Designing Biologically-Inspired Smart Building Systems: Processes and Guidelines. (December 2013) - Park, Daekwon; Bechthold, Martin
This paper investigates design processes of and guidelines for biologically-inspired smart building systems (BISBS). Within the functional and performance requirements of building systems, biologically-inspired design is explored as the key approach and smart technology as the enabling technology. The Soft Modular Pneumatic System (SMoPS) is developed as a design experiment in order to verify the effectiveness of the BISBS design process. Similarly to how independent cells coordinate with each other to undergo certain tasks in multicellular systems, the SMoPS consists of autonomous modules that collectively achieve assigned functions. Within the soft body of each SMoPS module, sensor, actuation, and control components are integrated which enables the module to kinetically respond to and interact with its environment. The modular design and hierarchical assembly logic contribute to creating a flexible as well as robust building system. Throughout the design process, prototyping, simulation, and animation are utilized as an iterative and diversified development method.